On reliability of inferring liquefied shear strengths from simple shear testing - Riccardo Fanni; David Reid; Andy Fourie (Soils and Foundations, 2022)
A laboratory study was carried out to compare the behaviour of loose tailings under simple shear loading using a torsional shear hollow cylinder device (TSHC) and a direct simple shear (DSS) device, with a focus on shear strength at high strains. This work was carried out on tailings for which the critical state line (CSL) had already been defined, to enable the results to be examined in a critical state framework. The testing indicated that the shear strengths measured at high strains by the DSS apparatus were significantly higher than those measured by the TSHC under undrained simple shear loading conditions. The likely more uniform and ideal simple shear conditions developing within the TSHC, along with the better agreement of results obtained using this equipment with the expected behaviour based on the test initial states and tailings’ CSL suggest that for loose specimens the DSS may overestimate shear strength at high strains. This observation was confirmed by comparing the results of this study with other published data where both CSL and DSS test results were available. The important implications of this observation for the design and analysis of tailings storage facilities (TSFs) in the context of laboratory measurement of liquefied strengths are outlined.